YhjX Regulates the Growth of Escherichia coli in the Presence of a Subinhibitory Concentration of Gentamicin and Mediates the Adaptive Resistance to Gentamicin - Zhou, Shuqin; Zhuang, Yijing; Zhu, Xiaojuan; Yao, Fen; Li, Haiyan; Li, Huifang; Zou, Xiaoguang; Wu, Jianhua; Zhou, Huifang; Nuer, Gulibaier; Huang, Yuanchun; Li, Shao; et al. (Frontiers in Microbiology, 2019)
The mechanisms of adaptive resistance to aminoglycosides of Escherichia coli (E. coli) still remain unclear. Our initial study found that expresssion of yhjX, a gene coding a putative transporter of the major facilitator superfamily, remarkably upregulated during first exposure to sub-inhibitory concentration of gentamicin. And the expression of yhjX was then down-regulated dramatically during second exposure to the gentamicin compared to the first exposure. In order to invesigate the effect of yhjX involved in adaptive resistance of E coli, in the present study, we constructed the yhjX deletion and complemented strains of E. coli ATCC25922. Results showed that yhjX deletion improved the growth of E. coli in the medium containing sub-inhibitory concentration of gentamicin. YhjX deletion mutant did not display adaptive resistance to sub-inhibitory concentration of gentamicin. Our findings imply that yhjX regulates the growth of Escherichia coli in the presence of sub-inhibitory concentration of gentamicin and mediates the adaptive resistance to gentamicin.